Quantification of physical activity with activity tracking after transfemoral aortic valve replacement (TAVR). (14th October 2021) - Zadrozny, M; Humpfer, F; Steffen, J; Fischer, J; Stocker, T; Theiss, H; Braun, D; Massberg, S; Hausleiter, J; Deseive, S
Abstract: Background and hypothesis: TAVR is a well-established, safe and effective therapy for severe symptomatic aortic stenosis (AS), but improvement of physical activity after TAVR is difficult to assess objectively. The aim of this study was to quantify improvement of physical activity with Activity Tracking after TAVR with special focus on the different low-gradient subtypes of AS. Methods: All patients who underwent TAVR for severe AS in our center between 01/2019 and 12/2019 were screened. Participants received an Activity Tracker for 7 days at two times: after hospital discharge following TAVR procedure and 6 months thereafter. The difference of mean daily steps was defined as study endpoint. Results: The analysis is based on 230 patients. The median age was 79.7 years with 53.7% male participants. The median aortic valve area (AVA) was 0.75 cm 2 and median mean pressure gradient was 38.7 mmHg (Table 1). The median amount of daily steps was 4409 [IQR 2581–7487] steps/day after hospital discharge and 5326 [IQR 3045–8668] steps/day 6 months thereafter. On a patient base, median difference of steps per day was Δ 529 [IQR −702–2152]). Whenever possible, patients were categorized into different subgroups of AS. Patients with high-gradient (HG) AS showed significant improvement in difference of daily steps at 6 months-FUP (Δ 951 [IQR −378–2.323], p<0.001), as well as patients with paradox low-flow-low-gradient (LFLG) AS (Δ 1392 [IQR −609–4444], p=0.02). Patients with classical LFLG AS also showed an improvement of daily steps at 6-months-FUP but without statistical significance (Δ 192 [IQR −687–770], p=0.79). Patients with a normal-flow-low-gradient (NFLG) AS have no significant difference in daily steps after 6-months and show a tendency of decline in daily steps at 6-months-FUP (Δ −300 [IQR −1334–1406], p=0.67) (Figure 1). Conclusions: This is the first study of this sample size to evaluate physical activity after TAVR with an objective and reproducible method. Overall, physical activity improved significantly 6 months after TAVR and daily steps per day increased in all subtypes of AS besides NFLG AS, where a tendency of decline in daily steps without statistical significance was shown. However the increase in daily steps did not reach statistical significance in classical LFLG AS patients. FUNDunding Acknowledgement: Type of funding sources: None.